CUGE: a screening instrument for alcohol abuse and dependence in students. - Van Den Bruel, A; Aertgeerts, B; Hoppenbrouwers, K; Roelants, M; Buntinx, F (2004)
OBJECTIVES: The prevalence of alcohol abuse on college campuses ranges from 7 to 17%. Frequent heavy drinkers place themselves and others at risk for a variety of adverse consequences and frequently remain undetected. Brief individual interventions result in a significant reduction on the number of drinks. Therefore, detection of students at risk is useful and desirable. The CUGE has been elsewhere described as a promising screening device for problem drinking in students. In order to determine the diagnostic value of this new questionnaire, we set up a validation study in a new and independent population of freshmen. METHODS: A cross-sectional diagnostic study. Participants were college freshmen of the Katholieke Universiteit Leuven. All students received a questionnaire, containing the CUGE, being the test of interest, and the CIDI as the reference test. RESULTS: The CUGE combines a very high sensitivity of 91% with a reasonable specificity of 76.3% in this validation group. CONCLUSIONS: The CUGE is an excellent screening device in this population of students. In addition, it is a short questionnaire with only yes or no questions. This makes the CUGE easily applicable as a part of broad routine questionnaires.